2015
DOI: 10.4238/2015.may.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence for high-molecular weight glutenin subunits (HMW-GS) in indigenous landraces and commercial cultivars of bread wheat of Pakistan

Abstract: ABSTRACT. Wheat flour quality is an important consideration in the breeding and development of new cultivars. A strong association between high-molecular weight glutenin subunits (HMW-GS) and bread making quality has resulted in the widespread utilization of HMW-GS in wheat breeding. In this study, we analyzed 242 lines of wheat, including landraces from the provinces of Punjab and Baluchistan, as well as the commercial varieties of Pakistan, to determine allelic variation in the Glu-A1, Glu-B1, and Glu-D1 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…In the literature, there are limited data concerning the relationship between quality traits and Glu-B1-13 + 16 and Glu-B1-13 + 19 subunits; therefore, further studies would be indispensable for the detailed investigation of this topic and to confirm that these subunits can be used as markers in marker-assisted breeding programs. Yasmeen et al (2015) reported that subunits Glu-B1-13 + 16 and Glu-B1-13 + 19 were observed in small numbers of Pakistani landraces. Earlier studies demonstrated that the frequency of Glu-B1-13 + 16 and Glu-B1-13 + 19 subunits is negligible in the global wheat collection and both these subunits are strongly related to good bread-making quality among the Glu-B1 alleles (Ikeda and Takata, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are limited data concerning the relationship between quality traits and Glu-B1-13 + 16 and Glu-B1-13 + 19 subunits; therefore, further studies would be indispensable for the detailed investigation of this topic and to confirm that these subunits can be used as markers in marker-assisted breeding programs. Yasmeen et al (2015) reported that subunits Glu-B1-13 + 16 and Glu-B1-13 + 19 were observed in small numbers of Pakistani landraces. Earlier studies demonstrated that the frequency of Glu-B1-13 + 16 and Glu-B1-13 + 19 subunits is negligible in the global wheat collection and both these subunits are strongly related to good bread-making quality among the Glu-B1 alleles (Ikeda and Takata, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the 1B/1R translocation has a negative effect on quality traits, especially for EDEV. Several authors reported that genotypes with 1B/1R score higher in GY, TKW, TW, and SV; however, dough made from their flour has poor quality due to their low EDEV and farinograph stability time Yediay et al, 2010;Rasheed et al, 2014;Yasmeen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the two loci present in durum wheat ( Glu-A1 and Glu-B1 ) in principle encode four GSs but, due to gene silencing, typically only one to three GSs are accumulated in the endosperm 9 . As these proteins have no known biological function other than providing a source of protein to the germinating seedling, their encoding genes show a quite high level of allelic diversity, a finding which has been widely exploited in wheat improvement 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The subunit 2* (ecoded by b allele) was determined the most frequently in four (50.0%) genotypes, followed by subunit null (encoded by c allele) in three (37.5%) and subunit 1 (encoded by d allele) in one (12.5%) wheat genotypes. The varying in frequency of glutenin allele in wheat cultivars were found in other research (Knežević et al, 1993;Yasmeen et al, 2015;Knezevic et al, 2016a). In three pair of eight wheat genotype the same composition of glutenin subunits were found.…”
Section: Resultsmentioning
confidence: 53%